PENGARUH PERSEPSI NASABAH TERHADAP PENGGUNAAN CASH DEPOSIT MACHINE (STUDI EMPIRIS PADA NASABAH BANK UMUM DI KOTA BANDA ACEH) - Rafdi, M Emil; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose in this research is to test the influences of customer perception on cash deposit machine (CDM) usage on general bank customers in Banda Aceh. Sample used in this research are 50 respondents which acquired by using incidental sampling technique. Questionnaire used as collecting data technique and data analyzed by using multiple linear regression. The result showed that partially and simultaneously, perceived ease of use and perceived usefulness were influence intention of use of CDM on general bank customers in Banda Aceh with 66,7%. Perceived usefulness influence tend to be bigger than perceived ease of use influence